Micro- and mesozooplankton responses during two contrasting summers in a coastal Antarctic environment - Garcia, Maximiliano Darío; Hoffmeyer, Monica Susana; López Abbate, María Celeste; Barría de Cao, María Sonia; Pettigrosso, Rosa E.; Almandoz, Gaston Osvaldo; Hernando, Marcelo P.; Schloss, Irene Ruth (Polar Biology)
Rapid climate-driven melting of coastal glaciersmay control plankton dynamics in the WesternAntarctic Peninsula. It is known that in Potter Cove, 25 deMayo/King George Island, phytoplankton is tightly coupledto meltwater input. However, no information onzooplankton is available in this regard. The aim of thisstudy was therefore to examine the structure and dynamicsof microzooplankton and mesozooplankton in two zones(the inner and outer Potter Cove) differently impacted byglacier melting during two contrasting austral summers(2010 and 2011). Microzooplankton composition differedbetween the two zones and years analyzed, and its totalbiomass was observed to be highest far from the glacierinfluence and during 2010. Mesozooplankton compositionand biomass were similar in the two zones and yearsanalyzed. Colder than usual conditions in the summer of2010 prevented glacier melting, thus favoring the developmentof an exceptional micro-sized diatom bloom(*190 lgCl-1 and [15 lg l-1 chlorophyll a), whichwas tightly followed by a maximum in large copepodabundance. After the bloom and in coincidence with intenseglacier melting, large diatoms and large copepodswere observed to be replaced by nanophytoplankton andmicrozooplankton (aloricate ciliates and dinoflagellates),respectively. In 2011, low phytoplankton abundance,probably controlled by high tintinnid biomass, was observedas a result of warmer temperatures than 2010 andlow-salinity waters. Large copepods appeared to have exerteda high grazing pressure on aloricate ciliates andheterotrophic dinoflagellates in 2011. Our results suggestthat whereas the joint effect of water temperature, salinityand phytoplankton availability as well as compositioncould be of primary relevance in structuring micro- andmesozooplankton community, zooplankton could be ofsecondary relevance in controlling phytoplankton biomassin Potter Cove during the two summers analyzed. Fil: Garcia, Maximiliano Darío. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico ...